ADAM23 is downregulated in side population and suppresses lung metastasis of lung carcinoma cells. Issue 4 (16th March 2016) - Ota, Masahide; Mochizuki, Satsuki; Shimoda, Masayuki; Abe, Hitoshi; Miyamae, Yuka; Ishii, Ken; Kimura, Hiroshi; Okada, Yasunori
Abstract : Cancer cells contain a small population of cancer stem cells or cancer initiating cells, which can be enriched in the side population (SP) after fluorescence activated cell sorting. To examine the members of the ADAM, ADAMTS and MMP gene families related to phenotypes of the SP and the main population (MP), we screened the expression of all the members in the propagated SP and MP of A549 lung adenocarcinoma cells, and found that the relative expression ratio of ADAM23 in the MP to the SP is most highly increased, but none of them are increased in the SP. A similar result on the ADAM23 expression was obtained with another cell line, Calu‐3 cells. Overexpression of ADAM23 inhibited colony formation, cell adhesion and migration, and knockdown of ADAM23 by shRNA showed the reverse effects. ADAM23‐mediated suppression of colony formation, cell adhesion and migration was greatly reduced by treatment with neutralizing anti‐ADAM23 antibody, anti‐αvβ3 integrin antibody and/or ADAM23 disintegrin peptide. Expression of cancer stem cell‐related genes, including AKRC1/2, TM4SF1 and NR0B1, was increased by knockdown of ADAM23. In addition, lung metastasis of A549 transfectants with different levels of ADAM23 expression was negatively regulated by the ADAM23 expression levels. Our data provide evidence that ADAM23 plays a role in suppression of cancer cell progression through interaction with αvβ3 integrin, and suggest that downregulation of ADAM23 in SP cells may contribute toward providing a cancer stem cell phenotype by facilitating the activity of integrin αvβ3. Abstract : Lung metastasis after intravascular injection of A549 lung adenocarcinoma cells with different ADAM23 expression levels into NOD/SCID mice was determined by bioluminescence imaging and histological examination of the whole lungs. As shown in this figure, the metastasis was inhibited at two weeks in the mouse group received ADAM23‐overexpressing cells and enhanced in that of ADAM23‐knockdown cells.